2018
DOI: 10.1038/s41598-018-27228-0
|View full text |Cite
|
Sign up to set email alerts
|

Parasite motility is critical for virulence of African trypanosomes

Abstract: African trypanosomes, Trypanosoma brucei spp., are lethal pathogens that cause substantial human suffering and limit economic development in some of the world’s most impoverished regions. The name Trypanosoma (“auger cell”) derives from the parasite’s distinctive motility, which is driven by a single flagellum. However, despite decades of study, a requirement for trypanosome motility in mammalian host infection has not been established. LC1 is a conserved dynein subunit required for flagellar motility. Prior s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 54 publications
(93 reference statements)
5
82
0
2
Order By: Relevance
“…TcMscS knockout strains exhibited considerably reduced motility and loss of infectivity. This is consistent with recent studies showing that motility is necessary for virulence in T. brucei (59). In trypanosomatids, flagellar beating and motility are regulated by Ca 2+ transients generated in a directional manner along the flagellum (60).The generation of Ca 2+ waves linked to the activation of mechanosensitive channels has been demonstrated in Chlamydomonas (61), tubular kidney cells (62,63), lung epithelial lining (64) and bone cells (21).…”
Section: Discussionsupporting
confidence: 90%
“…TcMscS knockout strains exhibited considerably reduced motility and loss of infectivity. This is consistent with recent studies showing that motility is necessary for virulence in T. brucei (59). In trypanosomatids, flagellar beating and motility are regulated by Ca 2+ transients generated in a directional manner along the flagellum (60).The generation of Ca 2+ waves linked to the activation of mechanosensitive channels has been demonstrated in Chlamydomonas (61), tubular kidney cells (62,63), lung epithelial lining (64) and bone cells (21).…”
Section: Discussionsupporting
confidence: 90%
“…T. brucei has a single flagellum that is essential for parasite viability, infection and transmission [35]. The flagellum drives parasite motility, which is necessary for infection of the mammalian host [4], and for transmission by the tsetse fly [5]. In addition to its canonical function in motility, the flagellum plays important roles in cell division and morphogenesis [68] and mediates direct interaction with host tissues [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its canonical function in motility, the flagellum plays important roles in cell division and morphogenesis [68] and mediates direct interaction with host tissues [9]. Moreover, recent work has demonstrated that the trypanosome flagellum is the site of signaling pathways that control the parasite’s response to external signals and are required for transmission and virulence [4, 1015].…”
Section: Introductionmentioning
confidence: 99%
“…Общеизвестно, что, наряду с такими высокоразвитыми, доступными лишь небольшому числу пользователей техниками, как аналитическая электронная микроскопия (Hemphill, Croft, 1997) и лазерная микроскопия и микродиссекция (Jones et al, 2004), в паразитологии активно используются стандартные рутинные методы оптической микроскопии, причем для ряда массовых задач, таких, например, как анализ фекального биоматериала на индикаторы инвазий (Petithory and Ardoin-Guidon, 1995), такие, например, как яйца Ascaris lumbricoides, Dicrocoelium dendriticum, Schistosoma sp., крючки для Echinococcus granulosus, личинки нематод, Strongyloides stercoralis, как правило, использование даже элементарных средств исследовательской микроскопии (специальные виды контраста, флуорохромирование и т.д.) является избыточным.…”
Section: Introductionunclassified
“…Пионером движения за демократизацию диагностики на основе безлинзовой микроскопии является Айдоган Озкан из UCLA. Были исследованы и внесены в базы данных для машинного обучения (обучение с учителем -supervised learning) морфометрические диагностические паттерны, релевантные для паразитологии, такие, как трипаносомы (возбудители сонной болезни) и малярийный плазмодий; в качестве образцов гельминтологической практики для свободноживущих круглых червей были исследованы и идентифицированы свободноживущие нематоды вида Caenorhabditis elegans (Coskun et al, 2011;Bishara et al, 2010Bishara et al, , 2012Shimogawa et al, 2018). Методы машинного обучения были реализованы с использованием волонтеров на базе пакетов типа BIOGAMES, созданных для решения этой задачи (Mavandadi et al, 2012;Ozcan, 2014).…”
Section: Introductionunclassified